PENGEMBANGAN PERANGKAT PEMBELAJARAN FISIKA MODEL INKUIRI TERBIMBING BERBANTUAN VIDEOSCRIBE PADA MATERI KALOR UNTUK MENINGKATKAN HASIL BELAJAR SISWA SMAN 1 KEDUNGWARU - Rahmawati, Fitria; W.W, Soegimin; Kardi, Soeparman (Universitas Negeri Surabaya, 2016)
The aim of this research is to develop physics learning material based on guided inquiry model completed video scribe at heat material to improve senior high school achievement. Development of Physics Learning Material is used Dick and Carey model, this research using one-group pretest-posttest design. Data were analyzed using descriptive analysis qualitatively and quantitatively. Validation results showed that learning material is feasible to be implemented, including: (a) lesson plan; (b) student worksheet; (c) student books; (d) evaluation instrument. The results of this research were analyzed and obtained: lesson plan was properly implemented, good student responses, all students interested in learning. Learning evaluation of knowledge, N-gain include knowledge aspect and critical thinking skills, showed high improvement. Concluded that, physics learning materials developed is feasible to implemented and it can improve the student achievement Penelitian ini bertujuan mengembangkan perangkat pembelajaran fisika berbasis model inkuiri terbimbing berbantuan videoscribe yang layak untuk meningkatkan hasil belajar siswa SMA pada materi kalor. Pengembangan perangkat pembelajaran menggunakan model Dick and Carey, perangkat pembelajaran diujicobakan pada sekelompok subjek dengan rancangan one group pretest-posttest design. Data yang diperoleh dianalisis secara deskriptif kuantitatif dan kualitatif. Hasil validasi perangkat pembelajaran menunjukkan perangkat pembelajaran layak untuk diimplementasikan, meliputi: (a) RPP; (b) LKS; (c) Buku Ajar; (d) Media videoscribe; dan (e) Tes Hasil Belajar. RPP terlaksana dengan baik, dan siswa memberikan respon positif terhadap pembelajaran. N-Gain pada aspek pengetahuan dan keterampilan berpikir kritis menunjukkan peningkatan dengan kategori tinggi. Kesimpulan dari penelitian ini yakni perangkat pembelajaran yang dikembangkan layak diimplementasikan dan dapat meningkatkan hasil belajar siswa.